Workshop Sosial Media Series : Mengambil Data dari Media Sosial Twitter - Sari, Ani Oktarini; Setiaji, Setiaji; Mardiana, Tati; Hasanah, Riyan Latifahul (Jurnal Abdimas Perbanas, 2024)
Social media was designed with the aim of expanding human social interaction using the internet and web technology. The large amount of information available in the public media gives rise to a variety of different opinions. To find out public sentiment on an exclusive topic, sentiment analysis can be carried out by collecting opinion data according to social media users. Therefore, Nusa Mandiri University carries out Community Service in the form of a Social Media Workshop Series: Retrieving Data from Twitter Social Media for JPRMI DKI Jakarta. The method used in this Community Service activity is in the form of interactive training in conveying theory, while the practical method uses simulation and question and answer methods. With this training, JPRMI DKI Jakarta members can help process and display data sourced from social media.